190k views
4 votes
PLEASE HELPP

Solve the following equation:
1/3(y-2) - 5/6(y+1) = 3/4 (y-3) - 2
1. 11/5
2. -11/ 5
3. 53/15

2 Answers

4 votes
The answer is 11/5 because when you add that up that’s what you get. #2
User Bub Espinja
by
5.6k points
3 votes

Answer:

  • 1. 11/5

Explanation:

Solving in steps:

  • 1/3(y-2) - 5/6(y+1) = 3/4 (y-3) - 2
  • 1/3y - 2/3 - 5/6y - 5/6 = 3/4y - 9/4 - 2
  • 1/3y -5/6y - 3/4y = 2/3 + 5/6 - 9/4 - 2
  • 1/12y(4 - 10 - 9) = 1/12(8 + 10 - 27 - 24)
  • y*(-15) = - 33
  • 15y = 33
  • y = 33/15
  • y = 11/5

Correct option is 1.

User Mikael Finstad
by
5.4k points